Editorial: Basic research in bladder cancer – refining the tools. 3rd IBCN seminars series1 - Black, Peter C.; Goebell, Peter; Kamat, Ashish M.; Nawroth, Roman; Seiler, Roland; Williams, Stephen B.; Schmitz-Dräger, Bernd J. (Urologic Oncology-Seminars and Original Investigations, 2019)
This editorial highlights submissions to part II of the 3rd IBCN Seminars Series particularly focusing on the tools required for conduction of translational research in bladder cancer. One of the submissions describe the ex vivo culture of primary tumor cells from N-methyl-N-nitrosourea-induced bladder tumors in rats and subsequent establishment of an immortalized cell line. In a next step the authors thoroughly characterize this cell line. They conclude that differentiation marker expression patterns observed in the original tumors are largely retained in the spheroids. Although new cancer models, such as organoid tissue cultures, hold great promise for studying cancer progression and might have a potential for development and selection of an optimal treatment, their limitations must be kept in mind. The second submission, therefore, critically questions the current role of organoid tissue culture as a predictive tool in urothelial cancer patients. The third manuscript of this series provides a broader overview of post-translational modification in bladder cancer is presented and how PTMs can be exploited as potential therapeutic targets. The 3 manuscripts featured in this issue demonstrate especially how basic research is being channeled to inform clinically actionable discoveries.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Basic research; Bladder cancer; International Bladder Cancer Network (IBCN); Tumor models